Access Control with Uncertain Surveillance - Balbiani, Philippe (IEEE/WIC/ACM International Conference on web intelligence, 2005)
We present a variant of the access control matrix model obtained by incorporating uncertain surveillance saying that "if subject s performs illegally action a on object o then the degree of likelihood that it will remain unpunished is equal to x". We then turn to the question whether the expressive power of the matrix model grows when enriching access control with uncertain surveillance. In connection with this enriched model, we also discuss the solvable and unsolvable cases of the major theme of computer security, namely the safety problem for access control matrices.